Morphological instruction and reading development in young L2 readers: A scoping review of causal relationships - Ke, Sihui (Echo); Zhang, Dongbo (Studies in Second Language Learning and Teaching, 2021)
This scoping review explores the causal relationship between morphological instruction and reading development in young L2 learners by synthesizing 12 primary studies published between 2004 and 2019 (N = 1,535). These studies focused on reading English as the target language and involved participants between kindergarten and Grade 12 from four countries (China, Egypt, Singapore, and the USA). Findings suggested that (a) morphological instruction led to consistent and positive gains in L2 children’s morphological awareness and vocabulary knowledge, and the effect sizes (Cohen’s ds) ranged from small to large; and (b) the relationship between morphological instruction and other outcomes such as phonological awareness, word reading accuracy, word reading fluency, spelling, and reading comprehension was inconclusive. Notably, transfer effects of L2 English morphological instruction on novel word learning in English or on reading development in an additional language were only examined and observed in four primary studies. Discussion was provided regarding future instructional and research design.